2015
DOI: 10.1177/194008291500800413
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Diversity of Evergreen and Deciduous Species During Natural Recovery Following Clear-Cutting in a Subtropical Evergreen-Deciduous Broadleaved Mixed Forest of Central China

Abstract: Clear-cutting has been a widespread commercial logging practice, causing substantial changes of biodiversity in many forests throughout the world. Forest recovery is a complex ecological process, and examining the recovery process after clear-cutting is important for forest conservation and management. In the present study, we established fourteen 20 m × 20 m plots in three recovery stages (20-year-old second growth, 35-year-old second growth and old growth) and explored the changes in evergreen and deciduous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(16 citation statements)
references
References 48 publications
2
14
0
Order By: Relevance
“…Moreover, soil conditions together explained more variations in community features than topographical conditions (Table and ). These results support the great importance of soil factors in determining the plant diversity and forest structure of the EDMBFs at local scale (Huang et al, ). Topographical conditions in the MLZ plot mainly impacted community features by determining the soil conditions, especially at small scale, where their effects are mostly shared.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Moreover, soil conditions together explained more variations in community features than topographical conditions (Table and ). These results support the great importance of soil factors in determining the plant diversity and forest structure of the EDMBFs at local scale (Huang et al, ). Topographical conditions in the MLZ plot mainly impacted community features by determining the soil conditions, especially at small scale, where their effects are mostly shared.…”
Section: Discussionsupporting
confidence: 84%
“…The EDMBFs are sensitive to climate conditions at regional scale (Ge & Xie, 2017;Givnish, 2002;Kröber, Heklau, & Bruelheide, 2015), while the key environmental conditions in affecting these forests at local scale may be either soil or topographical conditions (Fang et al, 2016;Huang et al, 2015;Song et al, 2014;Xu et al, 2015). In this study, we found that changes in habitat followed by shifts in soil conditions (Supporting Information Figure S3) led to substantial variations in community features among habitats (Figure 3), indicating that habitat-associated soil conditions were the major factors in determining the plant diversity and forest structure of the EDBMFs at local scale.…”
Section: Community Features Change With Habitat Typementioning
confidence: 99%
See 1 more Smart Citation
“…These forest ecosystems are known for both their quantity and quality of plant leaf litter (Guo et al, ), which greatly impacts underground organic matter (Yang et al, ) and soil microbial diversity (Ding et al, ; Hu, Jin, Liu, & Yu, ). In recent years, careful attention has been paid to the impacts of broad‐leaved forest conversion on plant species diversity (Huang et al, ) and soil labile organic matter (Chen et al, ; Yang et al, ), as well as differences in plant photosynthetic activity (Villar, Robleto, Jong, & Poorter, ) and soil nutrient requirements (Aerts, ; Givnish, ) between EBF and DBF. However, underground microbial diversity and their associated metabolic activities of EBF and DBF are poorly understood, particularly the soil fungal composition and related functional gene diversity.…”
Section: Introductionmentioning
confidence: 99%
“…As global climate change intensifies, ongoing monitoring could be valuable for documenting and understanding forest responses to climate change (Teixeira et al 2015;Mi et al 2016). The evergreen and deciduous broad-leaved mixed forest in China's subtropical mountains is complex and biologically diverse and is considered to be sensitive to changes in climate (Huang et al 2015a). In this type of forest, at higher latitudes, deciduous trees are dominant in the upper layers, while, evergreen broad-leaved species are less abundant and occupy the lower layer.…”
Section: Introductionmentioning
confidence: 99%